2016
DOI: 10.1007/s11517-016-1589-3
|View full text |Cite
|
Sign up to set email alerts
|

Multi-parametric study of temperature and thermal damage of tumor exposed to high-frequency nanosecond-pulsed electric fields based on finite element simulation

Abstract: High-frequency nanosecond-pulsed electric fields were recently introduced for tumor or abnormal tissue ablation to solve some problems of conventional electroporation. However, it is necessary to study the thermal effects of high-field-intensity nanosecond pulses inside tissues. The multi-parametric analysis performed here is based on a finite element model of liver tissue with a tumor that has been punctured by a pair of needle electrodes. The pulse voltage used in this study ranges from 1 to 4 kV, the pulse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 54 publications
(74 reference statements)
1
13
0
Order By: Relevance
“…However, it is a delicate balance between an effective ablation and thermal effects or damage. The occurrence of thermal injury during a regular IRE treatment and the impact of a metal stent on the local temperature distribution and thermal injury remains controversial 4,13,[16][17][18][19][20][21]23,26,[32][33][34] . Severe complications during IRE of a pancreas tumour were presumed to be related to heating of the metal stent in a case report 13 .…”
Section: Discussionmentioning
confidence: 99%
“…However, it is a delicate balance between an effective ablation and thermal effects or damage. The occurrence of thermal injury during a regular IRE treatment and the impact of a metal stent on the local temperature distribution and thermal injury remains controversial 4,13,[16][17][18][19][20][21]23,26,[32][33][34] . Severe complications during IRE of a pancreas tumour were presumed to be related to heating of the metal stent in a case report 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Gianulis et al 27 tested cytotoxic efficiency of nsPEF for different cancers and found no apparent correlation with cell types. Recent studies 28 , 29 showed that, beside nsPEF dosage, temperature is another important issue when applying nsPEF in practice. Pliquett et al 2 measured the real time Joule heating and proved that nsPEF ablation under a certain parameter (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…pulse duration of 300 ns and electric field strength of 40 kV/cm) produced no obvious heat production or temperature increase. Mi et al 28 expanded the measurement to a multi-parametric setting (i.e. nsPEF parameter ranging from 1 to 4 kV, pulse width ranging from 50 to 500 ns, and repetition frequency between 100 kHz and 1 MHz).…”
Section: Discussionmentioning
confidence: 99%
“…Theoretical simulations suggested that multiple pulses may cause Joule heating [ 17 ]. In order to determine whether heat played a part in the cellular response, the temperature rise in the cell suspension was measured using a thermocouple immediately after nsEP exposure (Guangzhou Sungun Meas.…”
Section: Methodsmentioning
confidence: 99%